2020
DOI: 10.1097/nmd.0000000000001173
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress During Pregnancy

Abstract: The prevalence and risk factors associated with peripartum psychological distress—a unifying factor among common mental disorders (CMDs)—are not widely understood in underresourced settings. Cross-sectional data were collected from 664 pregnant women who reported for antenatal care at any of one of the 11 midwife and obstetrics units in Cape Town, South Africa. The prevalence of prepartum psychological distress was 38.6%. Associated factors included low socioeconomic status as measured by asset ownership (odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…Our finding of the prevalence of mental distress among pregnant women in Myanmar was lower than studies from South Africa (38.6%) 26 and Brazil (43.1%) 10 , where the 20-item Self-Report Questionnaire (SRQ-20) was used to assess mental distress in pregnancy. Both studies applied the summed score of less than or equal to seven as non-distress and a score equal to or greater than eight as mental distress.…”
Section: Discussioncontrasting
confidence: 84%
“…Our finding of the prevalence of mental distress among pregnant women in Myanmar was lower than studies from South Africa (38.6%) 26 and Brazil (43.1%) 10 , where the 20-item Self-Report Questionnaire (SRQ-20) was used to assess mental distress in pregnancy. Both studies applied the summed score of less than or equal to seven as non-distress and a score equal to or greater than eight as mental distress.…”
Section: Discussioncontrasting
confidence: 84%
“…Taiwan is a moderate-to-high income country [ 44 ]. The prevalence of symptom distress is increasing among low-income groups [ 45 , 46 ]. We acknowledge that various patterns may exist, but more research is needed to understand the reasons behind a lack of “stable high” and “stable low” exhibiting among Taiwanese pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in three pre-COVID-19 studies conducted in Turkey, the mean TPDS scores of pregnant women ranged from 11.63 ± 6.40 to 23.66 ± 7.48 and the proportion of pregnant women at risk of distress was between 9.6% and 33% 22 , 23 , 42 . In a study conducted in Africa, the prevalence of pregnancy distress was reported to be 38.6%, while in a study conducted in the United States, 21.2% of women had pregnancy distress 20 , 43 .…”
Section: Discussionmentioning
confidence: 94%
“…This condition is referred to as pregnancy distress and has been attributed to various factors, including pregnancy-related physical and social changes, medical problems, fear of childbirth, and efforts to adapt to parenthood [16][17][18] . The prevalence of pregnancy distress varied between 23% and 38% in pre-COVID-19 studies19, 20. In studies conducted in Turkey, this figure ranged from 9% to 33% [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%